2009
DOI: 10.1080/00140130903141204
|View full text |Cite
|
Sign up to set email alerts
|

Studying the relationship between low back pain and working postures among those who stand and those who sit most of the working day

Abstract: A relationship between low back pain (LBP) and prolonged standing or prolonged sitting at work has not been clearly shown, despite its biological plausibility. Because sitting and standing postures vary as to duration and freedom to alternate postures, and standing postures vary as to mobility, associations between specific working postures and LBP were explored using multiple logistic regression. Associations between work factors and self-reported LBP during the previous 12 months that interfered with usual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(77 citation statements)
references
References 109 publications
1
74
0
2
Order By: Relevance
“…In the pilot's seat there was an increased prevalence of pain, the onset of pain was quicker and the intensity was greater (11). This has been investigated by others where those sitting in a fixed position had higher incidence of LBP compared to those who were allowed to move more freely (31). That there is a link between spinal posture and LBP is therefore well established, but the mechanics and biological processes in various postures that lead to LBP are not fully understood (20).…”
Section: Assessment Methodsmentioning
confidence: 99%
“…In the pilot's seat there was an increased prevalence of pain, the onset of pain was quicker and the intensity was greater (11). This has been investigated by others where those sitting in a fixed position had higher incidence of LBP compared to those who were allowed to move more freely (31). That there is a link between spinal posture and LBP is therefore well established, but the mechanics and biological processes in various postures that lead to LBP are not fully understood (20).…”
Section: Assessment Methodsmentioning
confidence: 99%
“…Quality assessment workers, for example, may stand for the entirety of their shifts (Hancock, 2005), potentially contributing to the development of lower limb, back, and shoulder pain (Tissot, Messing, & Stock, 2009). Sewing machine operators, on the other hand, are seated and bent forward while performing their work, increasing the likelihood of back, neck, and shoulder symptoms (Westgaard & Jansen, 1992;Sarder, Imrhan, & Mandahawi, 2006;Tissot, Messing, & Stock, 2009). …”
Section: Musculoskeletal Symptoms Among Factory Workersmentioning
confidence: 99%
“…Such work organization factors have been found to correlate with neck, back, and shoulder symptoms, particularly among female workers (Johansson & Rubenowitz, 1994;Bildt, Alfredsson, Michélsen, Punnett, Vingård, Torgen, et. al., 2000;Tissot, Messing, & Stock, 2009;Wang, Rempel, Hurwitz, Harrison, Janowitz, & Ritz, 2009;Wang, Harrison, Yu, Rempel, & Ritz, 2010).…”
Section: Musculoskeletal Symptoms Among Factory Workersmentioning
confidence: 99%
“…Prolonged standing has been identified as an ergonomic risk factor for body discomfort among electronic workers in this study. This has also been revealed by previous studies (Chandrasakaran et al, 2003;Chee et al, 2004;Tissot et al, 2009). Therefore, working process and posture of workers in part packaging and assembly should be investigated for related musculoskeletal discomfort.…”
Section: Resultsmentioning
confidence: 98%
“…Musculoskeletal disorders (MSDs) are considered to be a major occupational health problem and also affecting quality of work life, medical costs, efficiency at work and productivity in most workplaces (Health and Safety Executive, 2015). Industrial workers have been identified as high risk of developing MSDs (Aziz et al, 2015;Chandrasakaran et al, 2003;Chee et al, 2004;Tissot et al, 2009). Lu et al (2016) reported that manufacturing operators in Taiwan for the prevalence of MSDs was 31.8%.…”
Section: Introductionmentioning
confidence: 99%